Effect of microstructure on the nanotube growth by anodic oxidation on Ti-10Nb alloy - Luz, A. R. (2017)
Several papers have reported the grown self-organized nanotube arrays on pure Ti and its alloys to improve the surface of these materials for biomedical applications. The growth of nanotubes can be influenced by microstructure of material; however, few papers concerning this topic have been published. The aim of this work was to investigate the morphology, the cross-section view and the oxides in nanotube arrays in relationship to the microstructure of the Ti-10Nb alloy. The growth of nanotubes on the Ti-10Nb alloy obtained by anodic oxidation (AO). The Ti-10Nb alloy is composed by alfa and beta phases that were investigated by metallographic analysis, patterns of x-ray diffraction and EDS analysis. SEM images and EDS analysis revealed the morphology was composed by self-organized nanotube arrays on the alpha phase and walls with transversal holes on beta phase. X-ray patterns show crystalline oxides formation. Raman spectrum confirms the presence of anatase and Nb2O5 oxides. A significant contribution of the Nb2O5 was observed by bi-dimensional (x, y) Raman mapping, which also showed that the all oxide film was homogeneous oxide distributed on Ti-10Nb alloy. The nanostructured films have higher thickness in the beta than in the alpha phase, and have a small different in structure and oxide composition; as observed by SEM and Raman mapping. The results indicate that the microstructure of the Ti-10Nb affects the nanotubes morphology and the cross-section view, but the oxide formation was similar for all regions analyzed.